Updated catalogue of bony fishes observed in deep waters at Isla del Coco National Park and Las Gemelas Seamount, Costa Rica (Eastern Tropical Pacific) - Sánchez-Jiménez, Astrid (2018)
From 2006 to date the submersible DeepSee has been used to study the deep waters in and around Isla del Coco National Park, Costa Rica. Over these years, images and samples have been collected at depths between 50 and 450 m. Here we present a catalogue of bony fishes recorded by the submersible in deep waters of Isla del Coco, 500 km south-southwest of mainland Costa Rica, and at Las Gemelas Seamount within the designated Seamounts Management Area, 50 km southwest of Isla del Coco. A database with video-images of bony fishes was created from videos taken by the submersible’s high-definition digital camera from 2006 to 2015. Additional information on the distribution of fishes was obtained from 11 dives (24.3 hrs) using the remotely operated vehicle Hela at Las Gemelas Seamount during February 2012. Images of bony fishes were obtained during 376 dives (365 DeepSee dives plus 11 Hela dives) in 18 different locations, and here we report on a total of 85 taxa (i.e. putative species). In this catalogue we present images that are the first color photographs published for some species. In other cases, identifications were possible only to the level of genus (11), family (5) or order (1); hence the information is presented in terms of putative taxa. Four new records are reported for Isla del Coco: Leptenchelys vermiformis (Ophichthidae), Hyporthodus mystacinus (Serranidae), Kathetostoma averruncus (Uranoscopidae), and Symphurus diabolicus (Cynoglossidae). Depth ranges of twenty-six species are expanded beyond previously published records; three were observed in shallower water, twenty-two in deeper water and one was observed both shallower and deeper than in previous reports. As might be expected, increased bottom time with the submersible resulted in additions to the list of documented species. This highlights the importance of maintaining systematic research efforts in the deep waters around Isla del Coco, both for scientific purposes as well as conservation.